Role of shear wave elastography in assessment of placental elasticity in normal and high-risk pregnancies in third trimester - Imtiaz, Sheeza; Naz, Nasreen; Walid, Ayesha; Rahim, Anila; Waseem, Hira Fatima (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the elasticity of placenta using shear wave elastography in normal and high-risk pregnancies in the third trimester. Method: The prospective, observational study was conducted at the Dow Institute of Radiology, Dow University of Health Sciences, Karachi, from September 15, 2022, to January 15, 2023, and comprised singleton pregnant women during 28-40 weeks of gestation who were referred from the obstetric department. The subjects were divided into normal pregnancy group A and high-risk pregnancy group B. Risk factors include gestational hypertension, gestational diabetes, intrauterine growth restriction, placenta previa, morbidly adherent placenta, old primigravida, teen age and morbid obesity were noted. All the patients underwent grey scale, Doppler ultrasonography and shear wave elastography. Data was analysed using SPSS 26. Results: Of the 104 subjects, 78(75%) were in group A and 26(25%) were in group B. The overall mean age was 34.2±3.59 years. In group B, mean placental shear wave velocity was 2.34±1.17m/sec and elasticity was 24.41±25.51kPa compared to 1.42±0.55 m/sec and 13.6±10.23kPa in group A (p<0.05). Significant positive correlation was found between shear wave velocity and elasticity values in both groups (p<0.001). Conclusion: Shear wave elastography was found to be a useful technique in detecting placental stiffness, and can be used as an adjunct to the currently available ultrasonographic methods in high-risk pregnancies. Key Words: Shear wave, Elastography, Placenta, Velocity, Elastic modulus, High-risk pregnancy.